2017
DOI: 10.7729/92.1172
|View full text |Cite
|
Sign up to set email alerts
|

Using Films to Increase Cultural Competence in Working With LGBTQ Clients

Abstract: There is a dearth of research on effective strategies for teaching counselors-in-training how to work more effectively with LGBTQ clients. Experiential learning activities, such as watching films, can increase students' knowledge of their attitudes and beliefs about themselves and culturally diverse clients. This qualitative study explored, in the context of a sexuality and counseling course, how 27 students' awareness, knowledge, and skills were influenced by the use of two films, For the Bible Tells Me So an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Of the studies who reported demographic characteristics of participants ( n = 11), most participants were White, heterosexual, cisgender women. Interestingly, of the studies who reported demographics, three did not report information on sexual orientation (Finkel et al, 2003; Frick et al, 2017; Pearson, 2003) and two studies did not report information on race (Kauth et al, 2016; Pepping et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies who reported demographic characteristics of participants ( n = 11), most participants were White, heterosexual, cisgender women. Interestingly, of the studies who reported demographics, three did not report information on sexual orientation (Finkel et al, 2003; Frick et al, 2017; Pearson, 2003) and two studies did not report information on race (Kauth et al, 2016; Pepping et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of training recommendations, this area was afforded the most attention by study authors and had the greatest number of overlapping recommendations. The most commonly cited component was an opportunity for difficult dialogues and discussion ( n = 3; i.e., Craig et al, 2015; Frick et al, 2017; Weeks et al, 2018). Two other areas of agreement were the inclusion of first-hand accounts, such as panels ( n = 2; i.e., Frick et al, 2017; Leyva et al, 2014); and a skill rehearsal or role play component ( n = 2; i.e., Craig et al, 2015; Frick et al, 2017) to enhance professional skills with queer clients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The word competence is used because it implies having the capacity to function effectively. (p. 1) Related but distinct models appeared in fields such as healthcare (Campinha-Bacote, 2002;Kripalani et al, 2006); counseling (Frick et al, 2017;Kim and Lyons, 2003), social work (Cross et al, 1989); and education (Keengwe, 2010;Meaney et al, 2008). Interestingly, cultural competence is sometimes conceived as a characteristic of organizations (Cross et al, 1989), sometimes as possessed by an individual and sometimes as a quality of services provided (McManus, 1988), even within the same discipline, and sometimes by the same authors.…”
Section: What Is Cultural Competence?mentioning
confidence: 99%